Dynamic instability analysis of elastic-plastic beams - Liu, Yumin. (2008)
The primary objective of this study is to investigate analytically and numerically the dynamic instability, and furthermore to establish a dynamic instability theory of elastic-plastic beams subjected to transverse pulse load.